2021
DOI: 10.1111/2041-210x.13698
|View full text |Cite
|
Sign up to set email alerts
|

Double‐tagging scores of seabirds reveals that light‐level geolocator accuracy is limited by species idiosyncrasies and equatorial solar profiles

Abstract: 1. Light-level geolocators are popular bio-logging tools, with advantageous sizes, longevity and affordability. Biologists tracking seabirds often presume geolocator spatial accuracies between 186 and 202 km from previously innovative, yet taxonomically, spatially and computationally limited, studies. Using recently developed methods, we investigated whether assumed uncertainty norms held across a larger-scale, multispecies study.2. We field-tested geolocator spatial accuracy by synchronously deploying these w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 71 publications
(80 reference statements)
2
29
0
Order By: Relevance
“…This may be different, however, when estimating spatial repeatability due to the different spatial resolutions and measurement errors of each method (see Dingemanse et al, 2022). For example, geolocators can have large errors around location estimates (Halpin et al, 2021; Phillips et al, 2004), which may underestimate repeatability due to uncertainty when a bird reaches an exact location. Nonetheless, it is important to note the costs and limitations associated with each tracking method that is likely to be a constraint of the study system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be different, however, when estimating spatial repeatability due to the different spatial resolutions and measurement errors of each method (see Dingemanse et al, 2022). For example, geolocators can have large errors around location estimates (Halpin et al, 2021; Phillips et al, 2004), which may underestimate repeatability due to uncertainty when a bird reaches an exact location. Nonetheless, it is important to note the costs and limitations associated with each tracking method that is likely to be a constraint of the study system.…”
Section: Discussionmentioning
confidence: 99%
“…on a minute or hourly basis) and spatial accuracy (within ~150 m and 10 m, respectively) but until recently their mass restricted them to species of larger body size (Hobson et al, 2019). In contrast, GLS have low power requirements, allowing the devices to be considerably lighter (<1 g; Bridge et al, 2011), and are relatively cheap but provide only two locations per day with varying levels of spatial inaccuracy (Halpin et al, 2021; Phillips et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We have identified a location of aggregation in razorbills in the central North Sea, which is not clearly evident from at-sea densities of auks in winter based on survey data from 1980−2018 (Waggitt et al 2020). Although it is well-known that there are high levels of error associated with locations derived from geolocators, our methods of processing the data followed current best practice for minimising that error (Halpin et al 2021). Further, we extracted 50% kernel density contours from relatively high sample sizes of individuals from each colony, so we believe that our findings are reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Both species had high quality light curves throughout the non-breeding season, with the majority of transitions clearly identifiable. We then used 'probGLS' (Merkel et al 2016) to determine locations, a method shown to reduce the generally large error associated with geolocation (Phillips et al 2004, Halpin et al 2021. This method incorporates remotely-sensed environmental data, such SST, with light, activity and saltwater temperature recorded by the logger.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…during periods close to the spring and autumnal equinox and near the equator. 46 More generally, the variability in migratory schedules among individual birds creates deviations that infer problems in the comparison among flight paths. Long-distance migratory birds typically undertake sequences of nightly flights interspersed by extended multi-day stopovers to replenish energy reserves.…”
Section: Similarity Measures In Bird Flight Trajectoriesmentioning
confidence: 99%